2020
DOI: 10.1002/stc.2679
|View full text |Cite
|
Sign up to set email alerts
|

Formulation of human–structure interaction for vibration serviceability of steel–concrete composite floors

Abstract: Summary In this paper, an analytical model representing the human–structure interaction (HSI) system of steel–concrete composite floors under human vibrations is described and discussed. In the theoretical analysis, the human and composite floor are idealized as the subsystems represented by a linear oscillator model and the anisotropic rectangular plate, respectively. The analytical formula for the natural frequency and acceleration response of a steel–concrete composite floor with various boundary conditions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…In performing the theoretical analysis on the dynamic response due to walking excitations, the factors of human weight and the duration of single-step excitation were considered, which were also considered to develop the walk forcing function. As a result, the following Fourier series [42] defning the single-step walk forcing function F(t) was derived, as shown in Figure 15(a). For the single-step walking considered in the previous study, the frst six terms (n � 1-6) of the series were developed based on the experimental observations.…”
Section: Discussion Of Peak Coefcientmentioning
confidence: 99%
“…In performing the theoretical analysis on the dynamic response due to walking excitations, the factors of human weight and the duration of single-step excitation were considered, which were also considered to develop the walk forcing function. As a result, the following Fourier series [42] defning the single-step walk forcing function F(t) was derived, as shown in Figure 15(a). For the single-step walking considered in the previous study, the frst six terms (n � 1-6) of the series were developed based on the experimental observations.…”
Section: Discussion Of Peak Coefcientmentioning
confidence: 99%
“…The attenuation of vertical weighted vibration acceleration level (ΔVL Z ) at each floor was calculated by equation (4). A previous study showed that the vibration attenuation per story decreased with the rise of story.…”
Section: Discussionmentioning
confidence: 99%
“…The energy of floor vibration caused by these impact forces mainly distributes below 15 Hz. 3,4 In the measurement of vibration and structure-borne sound transmission, a standard tapping machine is used to simulate light-weight impact sources such as footsteps with shoes. 5 The tapping machine drops five equally spaced force hammers of 0.5 kg from a height of 40 mm.…”
Section: Introductionmentioning
confidence: 99%